Research progress on the key technologies and equipment for mechanized potato harvesting - Song, Zhiqiang; Ma, Zheng; Wang, Shuai (International Journal of Agricultural and Biological Engineering, 2025)
Potatoes are a staple food in many countries due to their rich nutritional content, including vitamins and carbohydrates, leading to their widespread cultivation globally. As China ranks first in the world in potato cultivation area and yield, making the crop vital to national food security, mechanized harvesting has become an indispensable solution for the sustainable development of the potato industry. This paper analyzes key technologies in potato mechanized harvesting, including efficient vine removal, low-loss and obstruction-reduced digging, high-efficiency cleaning and separation, and intelligent harvesting, based on an overview of China’s potato cultivation modes, mechanized harvesting methods and equipment. Furthermore, the study identifies gaps between Chinese potato harvesting equipment and that of European and American countries in terms of harvesting performance, intelligence level, and adaptability. Key challenges are also highlighted, such as significant regional variability, the lack of high-efficiency and low-loss separation devices, and difficulties in overcoming critical “chokepoint” technologies. Finally, the paper proposes future development directions for China’s potato harvesting equipment, emphasizing 1) synergistic multi-mode development, 2) research on flexible and low-loss separation devices, and 3) the integration of intelligent technologies. This study aims to provide references for key technologies and optimized design solutions, supporting the advancement of mechanized potato harvesting and promoting sustainable and efficient practices in the potato industry. Keywords: potato mechanized harvesting, vine removal, low-loss and obstruction-reduced digging, potato-soil separation, potato cultivation modes DOI: 10.25165/j.ijabe.20251805.9976 Citation: Song Z Q, Ma Z, Wang S. Research progress on key technologies and equipment for mechanized potato harvesting. Int J Agric & Biol Eng, 2025; 18(5): 1–14.